PERFORMANCE DRIVE TRAIN HYBRID SYSTEM IN GOKART VEHICLES - Prasetyo Dono Saputro (TRAKSI, 2019)
Drive train (power transfer) is a mechanism that removes the power generated by the engine to drive the wheels of vehicle. Transmission system is one important component in the drive train, whose main function is to channel out of the engine torque to the drive wheel. Transmission system is divided into 3 kinds: manual gear transmission, transmission hydrodinamik, and continuously variable transmission (cvt). And transmission used in ic engines hybrid go-kart is a CVT. In the design of hybrid drive train system on go-kart vehicles produce an analysis of torque, traction, and speed, are able to produce hybrid vehicles go-kart. And obtained τmax = 144,79 (N.m) , τmin = 1,38(N.m), Ftraksi max = 723,94(N), F traksi min = 6,89 (N) , Pmax = 2312,6 watt , Pmin = 74,6 watt, α max = 6,07 (m/s2) , α min = 0,02 (m/s2), on Yamaha AL115S(5TL3) engine, while in DC motor obtained by τmax = 14,25 (N.m) , τmin = 6,72 (N.m), Ftraksi max = 71,27(N), F traksi min = 33,58 (N) , α max = 1,14 (m/s2) , α min = 0,53 (m/s2).